2023
DOI: 10.1021/acs.chemmater.3c01669
|View full text |Cite
|
Sign up to set email alerts
|

Controllable Synthesis and Ultrahigh Anisotropic Single-Crystal Proton Conduction of a Hydrogen-Bonded Organic Framework

Abstract: Hydrogen-bonded organic frameworks (HOFs) with inherent welldefined hydrogen-bond networks are promising proton conduction materials. Herein, four three-dimensional HOFs were controllably assembled from 1,2,4,5-benzenetetracarboxylic acid and guanidinium of different chain lengths with certain ratios, in which GC-1 has undergone a water-induced single-crystal-to-single-crystal (SCSC) transformation to a more stable GC-2 with successive π−π stacking interactions. Notably, the ideal single-crystal sample of GC-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…As shown in Figure b, as the temperature rose from 30 to 75 °C under 80% RH, the conductivity increased continuously to 3.07 × 10 –2 S cm –1 , which was attributed to the acceleration of proton transfer with the temperature rising up (Figure b) . Although ordinary in comparison with the proton-conducting materials such as MOF, COF, HOF, etc., it is superior to typical proton-conducting materials in POMs , (Table S7). At last, the activation energy ( E a ) was evaluated by the Arrhenius equation [σ T = σ 0 exp­(− E a / k b T )], and calculations showed that E a at 80% RH was estimated to be 0.22 eV (Figure d), indicating that the Grotthuss mechanism is dominant during the process of proton conduction, given that E a is in the range from 0.1 to 0.4 eV .…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure b, as the temperature rose from 30 to 75 °C under 80% RH, the conductivity increased continuously to 3.07 × 10 –2 S cm –1 , which was attributed to the acceleration of proton transfer with the temperature rising up (Figure b) . Although ordinary in comparison with the proton-conducting materials such as MOF, COF, HOF, etc., it is superior to typical proton-conducting materials in POMs , (Table S7). At last, the activation energy ( E a ) was evaluated by the Arrhenius equation [σ T = σ 0 exp­(− E a / k b T )], and calculations showed that E a at 80% RH was estimated to be 0.22 eV (Figure d), indicating that the Grotthuss mechanism is dominant during the process of proton conduction, given that E a is in the range from 0.1 to 0.4 eV .…”
Section: Resultsmentioning
confidence: 99%
“…[153] Lun et al constructed four three-dimensional HOFs (GC-1, À 2, À 3, and À 4) with 1, 2, 4, 5benzenetetracarboxylic acid and guanidine and its derivatives, in which GC-1 undergoes a water-induced SCSC transformation to the more stable GC-2 with continuous π-π stacking (Figure 11b). [167] Notably, the GC-2 single-crystal samples are highly anisotropic, with a proton conductivity of 1.78×10 À 2 S cm À 1 along the [100] direction at ambient temperature and 98 % RH, which is 3-5 orders of magnitude higher than that along the [010] and [001] directions. This is associated with the formation of a continuous hydrogen bonding network and hydrophilic channel formation between the guanidine cation and the carboxylic acid anion along the a-axis direction.…”
Section: Proton Conductionmentioning
confidence: 99%
“…With some modifications to the initially reported method, GC-2 was prepared. 57 The specific synthetic operations are detailed in the Supporting Information.…”
Section: ■ Introductionmentioning
confidence: 99%